PENGEMBANGAN ALAT PERAGA BANDUL MATEMATIS BERBASIS MIKROKONTROLLER SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - M. Firdaus M. Firdaus; Hendar Sudrajad; M. Rahmad M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of this research was to produce prototype a valid mathematical pendulum props based microcontroller and student worksheet so that can be used properly as physics learning media for senior high school on simple harmonic motion material. Research and development which was used as research method. In this research, the development just till the validation step of the learning media and student worksheet. The data was obtained from validation result by 3 lecturers and 3 teachers as validator the validation was conducted in two phases, first phase was improvement and the second was assessment. The aspects which were assessed were the functionality of the equipment which got 3.53 of average point (very high category), the learning substance was 3.44 (very high category), the rashness was 3.58 (very high category), the esthetic and construction was 3.58 (very high category) and the safetynes was 3.50 (very high category). The aspect which were assessed from student worksheet were the content accuartion which got 3.67 (very high category), the presentation prosperity was 3.58 (very high category), the language prosperity was 3.50 (very high category), and the display prosperity was 3.72 (very high category). By all, each indicator of assessment in every aspect ware declared as valid in very high category. It can be concluded that mathematical pendulum based microcontroller and student worksheet were valid based on validation by the validators so that can be used properly as physics learning media for senior high school on simple harmonic motion material. As a recommendation, mathematical pendulum props can be equipped for testing by displaying several other quantities and doing practicality test to school.Keywords : Mathematical pendulum props based microcontroller, student worksheet physics learning media.